Análise de crescimento de Conyza sp., Digitaria insularis e Chloris sp. sob diferentes condições luminosas - Jakubski, Juliana Domanski (2020)
Conyza sp., Digitaria insularis and Chloris sp. are observed as weeds plants in agricultural areas, in addition, its resistance to herbicides and the high proliferation of these species make their management difficult. Management strategies are used to minimize the occurrence of damaged plants in agricultural areas, among them is the cultivation of cover plants, the choice of cultivating species with a robust canopy, shading the soil and already emerged weed plants, seeking to use its growth and development. However, some weeds may have their growth altered due to shading. The objective of the work was to evaluate the growth and development of Conyza sp., Digitaria insularis and Chloris sp. in two light conditions, full sun and artificially shaded. Experiment began with the germination of weed plant seeds in the laboratory for later transplants to the experimental units, which were 12-liter containers filled with soil. After the transplant and the adaptation carried out for 20 days in mild conditions of light and temperature, the experimental units were allocated to full sun and shade (50% shade), in an open randomized design, with four replications. During the 155 days after the transplant, destructive samples were collected for the estimates. The evaluations were carried out every 15 days, totaling 10 treatments. Height, dry matter, aerial part, leaf area, number of leaves, length of roots, dry matter of roots and green matter. To analyze these results, non-linear regressions were used. These variables also contributed to the construction of graphs for biological research of species, relative and absolute growth. For Conyza sp. an increase in the variables evaluated was observed in the shade compared to plants kept in full sun, the plants showed slow growth during a good part of the evaluation period. Digitaria insularis plants showed similar results among plants exposed to the sun and shade, with slow growth initially, in addition to a senescence period and two flowering phases. While for Chloris sp. shaded plants did not show good development in this condition, preferring environments with greater luminosity to develop, presenting slow initial growth in addition to flowering at the end of the evaluation period.